Faith, Knowledge, and Charity: Communication and Implementation in University Life / Iman, Ilmu, dan Amal: Komunikasi dan Implementasinya dalam Kehidupan Universitas - Zikri Fachrul Nurhadi; Dian Ranita; Ummu Salamah (UIN Antasari Banjarmasin, 2024)
This research is motivated by the results of a survey on the understanding of the motto